Ecological and Public Health Risk Assessment of Potential Toxic Elements in Road Dust from the Largest Industrial Zone in Da Nang City and Its Vicinity - Ngoc Bao, Le Quy; Hong Tinh, Nguyen Thi; Chanh, Nguyen Quoc; Lan Chau, Vo Thi; Kien, Tran Duc; Phuong Nhung, Huynh Thi; Thu Trang, Dinh Thi; Quang Truong, Le; Tuong Vi, Nguyen Le; Quoc Ba, Tran (VNU Journal of Science: Earth and Environmental Sciences, 2025)
This study investigates the ecological and human health risks associated with exposure to potential toxic elements ( PTEs ), including As , Cd , Mn , and Zn , in road dust from the largest industrial zone ( IZ ) in Da Nang City, Vietnam, and adjacent urban areas ( UA ). Ecological risk was assessed using the potential ecological risk index for individual elements ( Ei ) and the total potential ecological risk index ( PER ). Human health risk was evaluated through the non-carcinogenic hazard index ( HI ) and the total carcinogenic risk ( TCR ) for both children and adults. The findings revealed that ecological risk levels in the IZ were significantly higher than in the UA . However, both Ei and PER were classified as “Low” , with As being the predominant contributor. Health risk assessment indicated that HI and TCR values were consistently higher in children than in adults, and higher in the IZ compared to the UA . While HI values across all areas were below the threshold of 1 (indicating “Safe” ), specific IZ sites recorded HI values for children exceeding 0.7, suggesting potential concern. The mean TCR values for children in the IZ (1.49×10 -5 ) and UA (1.05×10 -5 ) exceeded the “Acceptable” range (1×10 -6 - 1×10 -5 ), whereas adult TCR values remained within permissible limits. As was the dominant contributor to both HI and TCR , followed by Pb . Compared with previous studies, the HI and TCR values we found were lower; however, potential risks remain, particularly for children, a vulnerable population due to physiological and behavioral factors. These results underscore the need for targeted management strategies focusing on As and Pb , coupled with emission control and environmental quality improvement, to reduce ecological risks and protect community health in industrial and urban settings. Keywords: Potential toxic elements , road dust, ecological risk, health risk, Da Nang.